In vitro pharmacological and rat pharmacokinetic characterization of LY3020371, a potent and selective mGlu2/3 receptor antagonist. (15th March 2017) - Witkin, Jeffrey M.; Ornstein, Paul L.; Mitch, Charles H.; Li, Renhua; Smith, Stephon C.; Heinz, Beverly A.; Wang, Xu-Shan; Xiang, Chuanxi; Carter, Joan H.; Anderson, Wesley H.; Li, Xia; Broad, Lisa M.; et al.
Abstract: Metabotropic glutamate2/3 (mGlu2/3 ) receptors are of considerable interest owing to their role in modulating glutamate transmission via presynaptic, postsynaptic and glial mechanisms. As part of our ongoing efforts to identify novel ligands for these receptors, we have discovered (1S, 2R, 3S, 4S, 5R, 6R)-2-amino-3-[(3, 4-difluorophenyl)sulfanylmethyl]-4-hydroxy-bicyclo[3.1.0]hexane-2, 6-dicarboxylic acid; (LY3020371), a potent and selective orthosteric mGlu2/3 receptor antagonist. In this account, we characterize the effects of LY3020371 in membranes and cells expressing human recombinant mGlu receptor subtypes as well as in native rodent and human brain tissue preparations, providing important translational information for this molecule. In membranes from cells expressing recombinant human mGlu2 and mGlu3 receptor subtypes, LY3020371.HCl competitively displaced binding of the mGlu2/3 agonist ligand [ 3 H]-459477 with high affinity (hmGlu2 Ki = 5.26 nM; hmGlu3 Ki = 2.50 nM). In cells expressing hmGlu2 receptors, LY3020371.HCl potently blocked mGlu2/3 agonist (DCG-IV)-inhibited, forskolin-stimulated cAMP formation (IC50 = 16.2 nM), an effect that was similarly observed in hmGlu3 -expressing cells (IC50 = 6.21 nM). Evaluation of LY3020371 in cells expressing the other human mGlu receptor subtypes revealed high mGlu2/3 receptor selectivity. In rat native tissue assays, LY3020371 demonstrated effective displacement of [ 3 H]-459477 from frontal cortical membranes (Ki = 33 nM), and functional antagonist activity in cortical synaptosomes measuring both the reversal of agonist-suppressed second messenger production (IC50 = 29 nM) and agonist-inhibited, K + -evoked glutamate release (IC50 = 86 nM). Antagonism was fully recapitulated in both primary cultured cortical neurons where LY3020371 blocked agonist-suppressed spontaneous Ca 2+ oscillations (IC50 = 34 nM) and in an intact hippocampal slice preparation (IC50 = 46 nM). Functional antagonist activity was similarly demonstrated in synaptosomes prepared from epileptic human cortical or hippocampal tissues, suggesting a translation of the mGlu2/3 antagonist pharmacology from rat to human. Intravenous dosing of LY3020371 in rats led to cerebrospinal fluid drug levels that are expected to effectively block mGlu2/3 receptors in vivo. Taken together, these results establish LY3020371 as an important new pharmacological tool for studying mGlu2/3 receptors in vitro and in vivo. This article is part of the Special Issue entitled 'Metabotropic Glutamate Receptors, 5 years on'. Highlights: LY3020371 is a highly potent and selective antagonist of human mGlu2/3 receptors. Highly consistent antagonist potencies exhibited in rat brain tissue assays. Dose-proportionate plasma and csf pharmacokinetics after i.v. dosing. Pharmacologically relevant csf concentrations for i.v. doses between 0.3 and 10 mg/kg. LY3020371 is a new tool for studying mGlu2/3 receptors in vitro and in vivo.